Serum levels of vitamin D in male partners of women with infertility in a tertiary hospital in Nigeria. (2023)
Globally infertility affects 8-12% of couples, with male and female causes contributing equally. Micronutrient's deficiency such as vitamin D has been implicated as a cause of infertility in animal studies, there is therefore the need to evaluate its role in humans. This study determined serum levels of vitamin D in males who were partners of patients presenting with infertility. This was a prospective cross- sectional study involving 170 consenting male partners of women presenting with infertility at the University College Hospital (UCH), Ibadan. A structured questionnaire was administered while blood sample and semen were collected for serum vitamin D assay and seminal fluid analysis (SFA) analysis. The data was entered into the Statistical Package for Social Sciences version 21 and statistical significance was set at less than 5%. Eighty-four (49.4%) participants had at least one abnormal parameter on SFA. The mean vitamin D level was higher in participants with normal SFA (34.4+12.6ng/ml) compared with abnormal SFA (32.8 + 15ng/ml). None of the participants had vitamin D deficiency, however the prevalence of vitamin D insufficiency among participants with abnormal and normal SFA was 62.5 % and 37.5% and this was statistically significant. (p = 0.01). Sperm progressive motility was the only SFA parameter associated with serum Vitamin D levels. (p-value = 0.03). This study showed that vitamin D insufficiency is associated with male infertility, therefore it may be added as an investigation for men with infertility and Vitamin D supplement be given where insufficiency or deficiency are noted.